2022
DOI: 10.3390/w14020258
|View full text |Cite
|
Sign up to set email alerts
|

Flow Intermittency Affects Leaf Decomposition and Benthic Consumer Communities of Alpine Streams: A Case Study along the Po River

Abstract: Streams and rivers are becoming increasingly intermittent in Alpine regions due to the global climate change and related increases of local water abstractions, making it fundamental to investigate the occurrence of supraseasonal drying events and their correlated effects. We aimed to investigate leaf litter decomposition, the C:N ratio of the litter, and changes in associated macroinvertebrate communities in three reaches of the Po River: One upstream, consistently perennial, a perennial mid-reach with high hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The higher bacterial and fungal diversity (increased evenness) [ 65 , 84 ] of oak leaf communities suggests that recalcitrance and high secondary compound content may require a more complex microbial community for initial decomposition and mineralization [ 85 ]. In our previous work of leaf litter decomposition along the Po river [ 42 , 43 ], we observed that chestnut leaves decomposed faster than oak, where the process continued, but delayed, during riverbed drying. Given the previous findings, combined with these microbial community changes, we suggest that terrestrial leaf-associated fungal taxa, along with early aquatic colonizers of in-stream litter accelerate decomposition for less recalcitrant leaves.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The higher bacterial and fungal diversity (increased evenness) [ 65 , 84 ] of oak leaf communities suggests that recalcitrance and high secondary compound content may require a more complex microbial community for initial decomposition and mineralization [ 85 ]. In our previous work of leaf litter decomposition along the Po river [ 42 , 43 ], we observed that chestnut leaves decomposed faster than oak, where the process continued, but delayed, during riverbed drying. Given the previous findings, combined with these microbial community changes, we suggest that terrestrial leaf-associated fungal taxa, along with early aquatic colonizers of in-stream litter accelerate decomposition for less recalcitrant leaves.…”
Section: Discussionmentioning
confidence: 98%
“…To measure leaf litter decomposition associated microbial communities, leaf litter bags were employed using two leaf species abundant in the watersheds and with distinct characteristics of quality/recalcitrance: chestnut ( Castanea sativa ) with 47.64 ± 0.47 C:N content at the beginning of the experiment, and oak ( Quercus robur ), 38.98 ± 0.47 initial C:N content, both collected in autumn after abscission. For more details regarding the experimental setting, including additional data on leaf litter decomposition rates and associated macroinvertebrates, please see previous publications by Gruppuso et al [ 42 , 43 ]. Three leaf bags per leaf species were collected on each sampling date, placed into individual plastic bags, and stored at −20°C until DNA extraction and microbial community sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…To measure leaf litter decomposition rates and associated microbial and invertebrate communities, leaf litter bags were employed using two leaf species abundant in the watersheds and with distinct differences in quality/recalcitrance: chestnut (Castanea sativa) with 47.64 ± 0.47 C:N content at the beginning of the experiment, and oak (Quercus robur), 38.98 ± 0.47 initial C:N content, both collected in autumn after abscission. For more details regarding experimental setting please see Gruppuso et al [28,29]. Three leaf bags per leaf species were collected on each sampling date, placed into individual plastic bags and stored at -20°C until DNA extraction and microbial community sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Gruppuso et al [8] provided new insights into the increasing climate-induced phenomena of riverbed drying in mountain streams and their correlated effects on leaf litter (in terms of decomposition rates and the C:N ratio) and the associated macroinvertebrate communities. Using leaf litter decomposition as a tool to assess river ecosystem quality and functional stream integrity, the authors compared this process in perennial and intermittent mountain stream reaches of the Po river (Northwest Italy) and evaluated the benthic community metrics (taxa richness, feeding group abundances).…”
Section: Summary Of This Special Issuementioning
confidence: 99%